Plant growth-promoting bacteria isolated from sugarcane improve the survival of micropropagated plants during acclimatisation - Michavila, Gabriela; Alibrandi, Pasquale; Cinà, Paolo; Welin, Bjorn; Castagnaro, Atilio Pedro; Chalfoun, Nadia Regina; Noguera, Aldo Sergio; Puglia, Anna Maria; Ciaccio, Mirella; Racedo, Josefina (Italian Journal of Agronomy, 2022)
The plant microbiome plays an important role in nutrient acquisition and buffering plant hosts against abiotic and biotic stress. During in vitro propagation of sugarcane, pathogenic microorganisms are eliminated and most of the beneficial endophytic microorganisms. The objective of this study was to isolate and characterise potential plant growth-promoting bacteria (PGPB) from sugarcane and to analyse their ability to improve the survival of micropropagated sugarcane plantlets during the acclimatisation stage. First, bacterial isolates from sugarcane were identified by partial 16S rDNA sequencing and tested for plant growth-promoting (PGP) features, such as inorganic and organic phosphate solubilisation nitrogen fixation, siderophore synthesis, indole-3-acetic acid production, tolerance to abiotic stress and antibiotics production. Then three bacterial strains with multiple PGP traits were independently applied to micropropagated seedlings of the sugarcane variety TUC 03-12 when the plants were transferred to a nursery for ex vitro acclimatisation. The effect of selected PGPB on survival rates of micropropagated plantlets was evaluated in three independent assays, using different batches of seedlings. Thirty days after inoculation, 182-Bacillus and 336-Pseudomonas isolates significantly improved the transferred plants survival rate. High variability in plant survival among independent experiments was observed, but treatments with the 336-Pseudomonas strain showed a low mortality rate (20%) in all assays. This procedure constitutes a biological tool to improve the survival of micropropagated plants during greenhouse acclimatisation. Furthermore, it provides an initial tool for selecting bacteria with possible PGP effects in the field. Highlights - A total of 162 isolates obtained from the rhizosphere, rhizoplane, roots, and stems of sugarcane were characterised for plant growthpromoting features and identified by partial 16S rDNA sequencing. - Two PGPBs strains isolated from sugarcane (182-Bacillus and 336-Pseudomonas) significantly improved survival rates of micropropagated seedlings during the acclimatisation stage. - Under different stress conditions, the 336-Pseudomonas strain improved the survival of micropropagated plants during the acclimatisation stage. Erratum in: 10.4081/ija.2022.2150